2019
DOI: 10.1002/mdc3.12811
|View full text |Cite
|
Sign up to set email alerts
|

Deep Brain Stimulation in Patients with Isolated Generalized Dystonia Caused by PRKRA Mutation

Abstract: View Supplementary Video 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Mutations in PRKRA cause young onset autosomal recessive dystonia parkinsonism ( 92 ). A response to GPi-DBS has been shown in a small number of cases of DYT16; a study of 2 patients showed an improvement in BFMDRS and walking times on gait analysis ( 93 ), and GPI-DBS produced a sustained improvement in cranial and limb dystonia over 10 years in one patient with a homozygous PRKRA mutation ( 94 ).…”
Section: Genetic Forms Of Dystonia and Response To Gpi-dbsmentioning
confidence: 99%
“…Mutations in PRKRA cause young onset autosomal recessive dystonia parkinsonism ( 92 ). A response to GPi-DBS has been shown in a small number of cases of DYT16; a study of 2 patients showed an improvement in BFMDRS and walking times on gait analysis ( 93 ), and GPI-DBS produced a sustained improvement in cranial and limb dystonia over 10 years in one patient with a homozygous PRKRA mutation ( 94 ).…”
Section: Genetic Forms Of Dystonia and Response To Gpi-dbsmentioning
confidence: 99%
“…For the study characteristics, a total of 33 cases had been described in 15 articles (Table 1) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. The majority of cases reported were from Brazil and European countries, with 18 cases (54.5%) and 14 cases (42.4%), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…These commonly involved extremities, oromandibular region, larynx, cervical region, and trunk. Parkinsonism was also developed in 15 cases (45.5%) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Isolated Focal Dystoniamentioning
confidence: 99%
See 2 more Smart Citations